Effect of nozzle depth to acoustic signals produced by a Ranque-Hilsch Vortex Tube / Wirachman Wisnoe and Khairil Muhaimin Abd Rahman - Wisnoe, Wirachman; Abd Rahman, Khairil Muhaimin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper aims to present the analysis of acoustic sound produced from a Ranque-Hilsch Vortex Tube. Two microphones are used to capture the sound produced at the hot and cold tubes. Different nozzle depths of the swirl generator are tested and different inlet pressure gages are applied. It is observed that, for one swirl generator, the sound produced contains a specific set of frequencies. These frequencies remain present when the inlet pressure is varied, while the magnitude of these frequencies changes. Different swirl generator produces different set of frequencies. These sets of frequencies-magnitudes represent acoustic signatures of the configurations. This acoustic signature is then linked with their thermofluid performance.